The psychosocial impact of orofacial pain in trigeminal neuralgia patients: a systematic review. Issue 7 (July 2018) - Melek, L.N.; Devine, M.; Renton, T.
Abstract: Trigeminal neuralgia (TN) is characterized by sharp, electric shock-like pain, which can be triggered by trivial stimuli. Although medical and surgical treatments are available for TN, some patients experience refractory pain, which has a significant impact on their quality of life. The aim of this systematic review was to determine the psychosocial impact of orofacial pain in patients with diagnosed TN. A search was initiated in three electronic databases (Embase, MEDLINE, PubMed) to identify potential studies for inclusion in the review. All types of study published in English that reported psychosocial measures using validated psychometric questionnaires were included. A total of 585 articles were retrieved from the search. These were screened thoroughly, leading to the selection of 13 articles for data extraction and final analysis. The results show the chronic overwhelming nature of TN, with pain levels varying from mild to severe. Psychometric scores indicated mild to moderate depression, moderate to severe anxiety, and moderate to severe functional limitation of daily life activities in TN patients. Therefore, psychological support within a multidisciplinary team is recommended for TN patients to help them cope better with their chronic disorder and to improve the efficacy of treatment.